(3GdPNjQIs - (3KGHJ Hf bQI Hf RgQhf GdMQGfj GdUCHrj, CHh GdMSf,J (B288 (3g` s
(3ChdgG (B:s
(3GdHGH GdChd ai LhGeY cdGe jSJYGf Hg Ydi MaX GdUMI s
(3BNQgG (B:s
(3BNQg eHJhQ hBNQ GdehLhO efg(B: (3hGeG GdCWYeI GdeDdaI GdRGFOI ai GdHGg aGdgQGjS Ydi gPg GdUaI s
(3fSNI KGdKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B98 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B101s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B96 s
(3eUOQ GbJfGA GdCUd (B:s
(3HQhSI (B- (3NQGLi RGOI (B((3WH (B12) s
Keywords: (3GdWHs